Action planning intervention to identify how to improve selection processes for internships - Juan A. Marin-Garcia; Eduardo González; Myriam Carrasco; Daniel Ros (WPOM : Working Papers on Operations Management)
In this research into participatory action research, by a team formed by researchers and people in charge in various areas of several multinational companies, we reflected on the advantages and disadvantages of internships and we proposed a procedure for companies to improve the recruitment and selection of industrial engineers, while strengthening relationships between the university and companies, attracting students’ interest, improving their professional competences and providing evidence for their students’ real learning to degree managers at the same time.